Improving Outcomes in Breast Cancer for Low and Middle Income Countries - Yip, C.H.; Buccimazza, I.; Hartman, M.; Deo, S.V.S.; Cheung, P.S.Y. (Springer Verlag (Germany), 2015)
Breast cancer is the most common cancer in women world-wide. Incidence rates in low- and middle-income countries (LMICs) are lower than in high income countries; however, the rates are increasing very rapidly in LMICs due to social changes that increase the risk of breast cancer. Breast cancer mortality rates in LMICs remain high due to late presentation and inadequate access to optimal care. Breast Surgery International brought together a group of breast surgeons from different parts of the world to address strategies for improving outcomes in breast cancer for LMICs at a symposium during International Surgical Week in Helsinki, Finland in August 2013. A key strategy for early detection is public health education and breast awareness. Sociocultural barriers to early detection and treatment need to be addressed. Optimal management of breast cancer requires a multidisciplinary team. Surgical treatment is often the only modality of treatment available in low-resource settings where modified radical mastectomy is the most common operation performed. Chemotherapy and radiotherapy require more resources. Endocrine therapy is available but requires accurate assessment of estrogen receptors status. Targeted therapy with trastuzumab is generally unavailable due to cost. The Breast Health Global Initiative guidelines for the early detection and appropriate treatment of breast cancer in LMICs have been specifically designed to improve breast cancer outcomes in these regions. Closing the cancer divide between rich and poor countries is a moral imperative and there is an urgent need to prevent breast cancer deaths with early detection and optimal access to treatment.